1990
DOI: 10.1111/j.1442-200x.1990.tb00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Bacteriuria in Japanese School Children

Abstract: Bacteriuria was screened among 28,202 healthy school children, 14,575 boys and 13,627 girls, by dipstick and dipslide methods and also by pour plate culture. The prevalence of bacteriuria was 0.06% in boys and 0.52% in girls after the third screening. A high rate of false negative results with the dipstick test and a high rate of false positive results with the dipslide culture method using Microstix‐3 were observed. About 60% of screened children continued to have bacteriuria persistently for 9 months after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In our study, the number of normal cases of RNC or VCUG in children under co-trimoxazole therapy was 1.2 times more than in those on cephalexin, but there was no significant difference between the two groups. Similar to our findings, Neilson stated that 10 to 35% of vesicular reflux cases had underlying malformations (27).Litaka et al also found that 21% of children with permanent bacteriuria had anomalies (28).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the number of normal cases of RNC or VCUG in children under co-trimoxazole therapy was 1.2 times more than in those on cephalexin, but there was no significant difference between the two groups. Similar to our findings, Neilson stated that 10 to 35% of vesicular reflux cases had underlying malformations (27).Litaka et al also found that 21% of children with permanent bacteriuria had anomalies (28).…”
Section: Discussionsupporting
confidence: 90%
“…In three papers which had previously used lower diagnostic thresholds [ 16 , 20 , 21 ], I recalculated their data using ≥ 10 5 cfu/ml. I rejected one study that had counted proteus contamination as UTI [ 31 ], another because of unacceptable design features [ 32 ], one because of selection bias [ 18 ], and one because the data was insufficient to reanalyse [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Univariate logistic regression revealed an association of outliers with lower categories of internal and external validity (internal ≤ 50%: OR = 15.9, 95% CI 1.1 to 233.2, external ≤ 75%: OR = 4.2, 95% CI 1.2 to 15.1). Therefore, studies in the lowest categories of internal or external validity (≤50%) were excluded from further sub-group analysis and meta-regression (n = 12, references: [36,37,44,62,71,72,77,78,82,83,88,89]).…”
Section: Resultsmentioning
confidence: 99%
“…Univariate logistic regression revealed an association of outlier studies with lower categories of external validity (external ≤ 50%: OR = 32, 95% CI 2.3 to 447). Studies in the lowest category (≤50%) of internal validity (n = 1, reference: [81]) and external validity (n= 6, references: [37,62,71,80,83,89]) were excluded from the analysis. Sensitivity and specificity were correlated after exclusion (Spearman ρ = -0.635), but remained heterogeneous (Q = 368 and 1799, df 34), as did the ln(DOR) (Q = 64, df 34).…”
Section: Resultsmentioning
confidence: 99%